Studi Kebijakan; Tinjauan Teoritis Peran Analisis Dalam Proses Kebijakan Publik - Gedeon, Hendrikus Tri Wibawanto (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2005)
The role of policy analyst in policy making process constitute an important factor that determine the success or the failure of public policy procuded and implemented. Therefore, in this article, the writter tries to elaborate it just as a throught to add insight to our analyst to know clearly how its role in policy making process.